A meso–meso directly linked porphyrin dimer-based double D–π–A sensitizer for efficient dye-sensitized solar cells1. Issue 18 (4th March 2015) - Zhang, Tao; Qian, Xing; Zhang, Peng-Fei; Zhu, Yi-Zhou; Zheng, Jian-Yu
<x xml:space="preserve">Abstract</x> A novel double D–π–A branched dye (JY07) was synthesized and applied as a sensitizer for DSSCs.